2019
DOI: 10.3390/mi10010054
|View full text |Cite
|
Sign up to set email alerts
|

Spray-On Liquid-Metal Electrodes for Graphene Field-Effect Transistors

Abstract: Advancements in flexible circuit interconnects are critical for widespread adoption of flexible electronics. Non-toxic liquid-metals offer a viable solution for flexible electrodes due to deformability and low bulk resistivity. However, fabrication processes utilizing liquid-metals suffer from high complexity, low throughput, and significant production cost. Our team utilized an inexpensive spray-on stencil technique to deposit liquid-metal Galinstan electrodes in top-gated graphene field-effect transistors (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The nozzle directs a stream of particles onto a substrate until the particles cover the surface with a complete film. This process is compatible with a variety of substrates, as seen in prior work [ 52 , 54 , 55 , 56 , 59 , 62 , 63 , 64 , 65 , 66 ]. While others have shown that patterning is possible using a directed laser to ablate liquid metal from the surface [ 53 ], here we make use of vinyl stencils (also commonly used in the crafting community) adhered to the substrate to pattern the metal.…”
Section: Resultsmentioning
confidence: 69%
“…The nozzle directs a stream of particles onto a substrate until the particles cover the surface with a complete film. This process is compatible with a variety of substrates, as seen in prior work [ 52 , 54 , 55 , 56 , 59 , 62 , 63 , 64 , 65 , 66 ]. While others have shown that patterning is possible using a directed laser to ablate liquid metal from the surface [ 53 ], here we make use of vinyl stencils (also commonly used in the crafting community) adhered to the substrate to pattern the metal.…”
Section: Resultsmentioning
confidence: 69%
“…Moreover, the scraping technique can be automated by mounting the needle to the printhead of a 3D printer, as illustrated in Figure 11. In addition to the transmission line and antenna demonstrated here, this method of spraying LM was used to create LM contacts for a graphene transistor [27].…”
Section: Discussionmentioning
confidence: 99%
“…By spraying through a stencil, electrically conductive features can be rapidly produced onto a variety of substrates. This technique has been used to manufacture electrodes, [87,88] inertial and strain sensors, [84,89] wireless power transmission coils, [90] and connections for thermal energy harvesters. [91] Using a stencil (which deviates from true direct-write techniques) also enables patterning on substrates with complex topography.…”
Section: Spray Patterningmentioning
confidence: 99%